Lead isochron dating of the Seton Formation, East Arm of Great Slave Lake, Northwest Territories - Cumming, G. L. (Canadian Journal of Earth Sciences, 1980)
Dating of "spilitic" basalts from the Proterozoic Seton Formation by the Pb/Pb method yields an age of 1804 ± 23 Ma (2σ), in excellent agreement with Rb–Sr data on the same rocks, when the latter ages are calculated with currently accepted decay constants. It seems unlikely that spilitization could have reset both the Rb–Sr and Pb/Pb systems to yield exactly the same ages with no geologic scatter about the isochrons in either case, and, therefore, it may be that the isochrons represent the true age of deposition of the lavas.